2020
DOI: 10.1002/jsfa.10371
|View full text |Cite
|
Sign up to set email alerts
|

Ensiling of whole‐plant hybrid pennisetum with natamycin and Lactobacillus plantarum impacts on fermentation characteristics and meta‐genomic microbial community at low temperature

Abstract: BACKGROUNDThe aim of the current research was to clarify the impacts of the ensiling of whole‐plant hybrid pennisetum with natamycin and Lactobacillus plantarum on fermentation characteristics and the meta‐genomic microbial community at low temperatures.RESULTSDuring the ensiling process, lactic acid (LA) and lactic acid bacteria (LAB) significantly (P < 0.05) increased and acetic acid (AA), water‐soluble carbohydrate (WSC), ammonia total nitrogen (NH3‐N), and yeast significantly (P < 0.05) reduced in tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 20 publications
3
14
0
Order By: Relevance
“…Previous studies have focused primarily on the effect of additives to P. sinese silages, but little is currently understood regarding the effect of additives on the microbiome of the resultant silage ( Li et al, 2014 , 2018a , 2018b , 2019a , 2020 ; Li L. et al, 2017 ; Wu et al, 2020 ). Currently, only a limited number of studies have examined the effects of additives on the fermentation quality and microbial diversity of P. sinese silage ( Dong et al, 2020 ; Shah et al, 2020 ). It is of note that these studies have focused on specific P. sinese cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have focused primarily on the effect of additives to P. sinese silages, but little is currently understood regarding the effect of additives on the microbiome of the resultant silage ( Li et al, 2014 , 2018a , 2018b , 2019a , 2020 ; Li L. et al, 2017 ; Wu et al, 2020 ). Currently, only a limited number of studies have examined the effects of additives on the fermentation quality and microbial diversity of P. sinese silage ( Dong et al, 2020 ; Shah et al, 2020 ). It is of note that these studies have focused on specific P. sinese cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, sugarcane presents high lactic acid production and a fast pH drop (Custódio et al, 2016), which also result in lowered natamycin effectiveness during fermentation. Shah et al (2020) reported lower yeast counts in Napier grass silage treated with natamycin for 60 days than in untreated silage. Additionally, the authors reported lower lactic acid levels than those of our silages.…”
Section: Discussionmentioning
confidence: 90%
“…As observed, silage treated with natamycin showed the lowest N 2 O production as well as the highest protein content. Shah et al (2020) reported lower protein degradation in elephant grass silage treated with natamycin than in untreated silage. It is possible that the presence of natamycin and acetic acid impaired protein metabolization by yeasts.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Antifungal supplements are mostly used to hinder the growth of yeasts, fungi, and other undesirable microorganisms to improve fermentation of the silage (Shah et al, 2020b). Yeast has long been considered to be the main microorganism that causes aerobic deterioration in silage because the aerobic deterioration of silage is closely related to the metabolism of the main yeast strain (da Silva et al, 2020).…”
Section: Microbial Community Compositionmentioning
confidence: 99%